2021
DOI: 10.1021/acs.jafc.0c06562
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive Study of In Situ Sensing and Swabbing Detection Based on SERS-Active Gold Nanobush–PDMS Hybrid Film

Abstract: Surface-enhanced Raman scattering (SERS) with fast and intuitive property has been extensively utilized in the field of food safety. Here, we demonstrated a novel noble metal–polymer hybrid film as a SERS substrate for food fungicide analysis. Benefiting from its transparency and flexibility, poly­(dimethylsiloxane) (PDMS) film was chosen as a versatile supporting matrix to grow gold nanobushes (Au NBs) through a seed-mediated process. The as-prepared AuNB–PDMS hybrid film performed satisfactorily in testing 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 42 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Plasmonic NPs are incorporated into polymer matrices to design more user-friendly, highly robust, and flexible optical platforms while preserving the optical properties of plasmonic NPs. A wide range of plasmonic-polymer nanocomposites has been developed by combining AuNPs or AgNPs and polymers such as agarose, chitosan, and poly­(methyl methacrylate) (PMMA) for SERS-based optical sensing, imaging, and photothermal applications. , Plasmonic-polymer nanocomposites can synergistically benefit from the excellent optical properties of plasmonic NPs and the wide range of mechanical and chemical properties of polymers, rendering various functionalities. , For instance, plasmonic nanocomposites of macroporous poly- N -isopropylacrylamide (pNIPAM) hydrogel loaded with gold nanorods have been used as biocompatible, SERS substrates for label-free in situ probing of quorum sensing in biofilms . Chitosan complexed with plasmonic NPs have been widely used as biocompatible optical substrates due to their excellent biocompatibility, biodegradability, and non-toxicity. ,, Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic NPs are incorporated into polymer matrices to design more user-friendly, highly robust, and flexible optical platforms while preserving the optical properties of plasmonic NPs. A wide range of plasmonic-polymer nanocomposites has been developed by combining AuNPs or AgNPs and polymers such as agarose, chitosan, and poly­(methyl methacrylate) (PMMA) for SERS-based optical sensing, imaging, and photothermal applications. , Plasmonic-polymer nanocomposites can synergistically benefit from the excellent optical properties of plasmonic NPs and the wide range of mechanical and chemical properties of polymers, rendering various functionalities. , For instance, plasmonic nanocomposites of macroporous poly- N -isopropylacrylamide (pNIPAM) hydrogel loaded with gold nanorods have been used as biocompatible, SERS substrates for label-free in situ probing of quorum sensing in biofilms . Chitosan complexed with plasmonic NPs have been widely used as biocompatible optical substrates due to their excellent biocompatibility, biodegradability, and non-toxicity. ,, Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…From these results, it can be observed that the as-prepared flexible SERS substrates exhibit outstanding uniformity and excellent reproducibility. Moreover, comparisons of the limits of detection, enhancement factors and signal reproducibilities between the Ag NPs@W-PDMS SERS substrate and other flexible SERS substrates are shown in Table S1, indicating that the Ag NPs@W-PDMS SERS substrate has excellent performance featuring a large enhancement factor, large-scale uniformity, and excellent spectral reproducibility. …”
Section: Resultsmentioning
confidence: 99%
“…Such values are lower than the thresholds of TBZ (20 μg/mL) and CA (100 mg/kg) in national regulations. 62,63 Meanwhile, such quantitative and sensitive SERS detections of 58 assembling gold nanorods 0.991 216 ng/mL 50−1000 ng/mL lemon juice SERS 59 Fe 3 O 4 @GO@Ag 0.962 40 ng/cm 2 4 ng/cm 2 −40 μg/cm 2 fruit peels SERS 61 Ag-Au-IP6-Mil-101(Fe) 0.986 50 ng/mL 1.5−75 ppm juice sample SERS 64 Au NBs−PDMS hybrid film 0.98 0.64 ng/mL 10 −4 −10 −9 g/mL cherry HPCL 65 hydroxyl TBZ and CA were evaluated by comparing them with some previous reports. As illustrated in Tables 1 and 2, this work gave out better values of R 2 and LODs than other investigations and it can be peculiarly applied to deeply processed foods by straightforward wiping.…”
Section: ■ Results and Discussionmentioning
confidence: 99%